Traditional Fishing Gears, Fish Catch and Species Composition of Selected Floodplain Wetlands of Lower Gangetic Plains, West Bengal, India - Sandhya, K. M.; Roy, Aparna; Hassan, M. A.; Kumari, Suman; Mishal, P.; Lianthuamluaia, L.; Kumar, Vikash; Aftabuddin, M.; Bhattacharjya, B. K.; Meena, D. K.; Ali, Y.; Naskar, B. (Fishery Technology, 2019)
Floodplain wetlands (locally called as beels) arebiologically sensitive habitats playing vital role infish recruitment as well as acting as nursery groundfor fishes and play an important role in the ruraleconomy of West Bengal. Catch composition anddetails of fishing gears used in eight beels from fourdistricts of West Bengal were documented. Gearsbased on their operation were categorised into activeand passive fishing gears. Use of these gears werefound to vary according to water depth, season,water area, type of fish species, availability of rawmaterial for gear fabrication etc. The socio-economicbackground of the fishers as well as their traditionalknowledge in fishing is also very important in theselection of gears. Most of the fishers were usinggears made with netting material of nylon forcatching the fishes. A total of 12 gear types alongwith their details, gear efficiency in terms of the typeof species caught and the catch per day wererecorded. Average fish catch/day was maximum forBerjal which varied from 75-105 kg comprising ofstocked fishes like Indian Major Carps, Exotic carpsas well as indigenous fishes. Use of small meshednets was recorded in this region which may lead toimbalances in fish stocks affecting icthyodiversity aswell as sustainable exploitation of fishes. Creatingawareness among the beel fishers on the adverseeffects of fine mesh nets on biodiversity was feltnecessary.